2014
DOI: 10.1007/s00467-014-2884-6
|View full text |Cite
|
Sign up to set email alerts
|

Demographics of paediatric renal replacement therapy in Europe: a report of the ESPN/ERA–EDTA registry

Abstract: Considerable variation exists in the current demographics of children treated with RRT across Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 19 publications
8
91
0
10
Order By: Relevance
“…In fact, the two regions with better social and economic indicators (South and Southeast) were those with the best renal transplantation numbers in this collection of data. These results support the concept that efficiency in kidney transplants in children is linked to macroeconomic indicators, with more transplants in more affluent regions, an observation that has also been made in developed countries such as the US and Europe [18][19][20]. Another interesting point revealed in the multivariable analysis is that the possible effect of the number of transplant centers per million population had a lower influence on the outcome in a model containing region, age, and GDP.…”
Section: Resultssupporting
confidence: 74%
“…In fact, the two regions with better social and economic indicators (South and Southeast) were those with the best renal transplantation numbers in this collection of data. These results support the concept that efficiency in kidney transplants in children is linked to macroeconomic indicators, with more transplants in more affluent regions, an observation that has also been made in developed countries such as the US and Europe [18][19][20]. Another interesting point revealed in the multivariable analysis is that the possible effect of the number of transplant centers per million population had a lower influence on the outcome in a model containing region, age, and GDP.…”
Section: Resultssupporting
confidence: 74%
“…[5][6][7] Data from national and regional renal registries in Europe show that CAKUT are the leading cause of endstage renal disease (ESRD) in children, accounting for 41.3% of children that receive renal replacement therapy (RRT). 8 Data from the European Renal AssociationEuropean Dialysis and Transplant Association Registry consisting of >200,000 patients undergoing RRT, revealed that the estimated median age of RRT initiation was 31 and 61 years in patients with and without CAKUT, respectively. 9 The age of onset of RRT was lowest in patients with renal dysplasia (16 years) and generally varied within CAKUT sub-phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas McDonald et al [178] reported a slightly lower mortality rate of 4.8 per 100 patient-years among children receiving Pediatric Nephrology DOI 10.1007/978-3-642-27843-3_62-1 # Springer-Verlag Berlin Heidelberg 2015 hemodialysis than among those receiving PD (5.9 %), survival rates of age-matched patients treated in Italy either with PD or with hemodialysis [286] and of those reported by Wong et al [316], by the United States Renal Data System [278] and by the European pediatric renal replacement therapy registry (ESPN/ ERA-EDTA registry [58]), did not differ between the two modalities.…”
Section: Patient and Technique Survivalmentioning
confidence: 92%